The public production of medicines compared to the National Policy of Medicines and the burden of disease in Brazil - Tatiana Aragão Figueiredo; Joyce Mendes de Andrade Schramm; Vera Lúcia Edais Pepe (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: The public production of medicines in Brazil by Government Pharmaceutical Laboratories has once again become the object of incentives, and Industrial Development Partnerships are one of the mechanisms adopted for the production of strategic medicines for the Brazilian Unified National Health System (SUS). Considering that burden-of-disease studies have been used as a tool to define priority and essential medicines, the article compares the product portfolios of the country's Official Pharmaceutical Laboratories (OPL) and the list of strategic medicines for the SUS and burden of disease in Brazil in 2008. Of the 205 strategic medicines for the SUS and 111 from the portfolios, 73% and 89%, respectively, are on the National List of Essential Medicines (RENAME 2014). Some strategic medicines for the SUS are already produced by OPL and feature the selection of cancer drugs and biologicals. The current study contributes to the discussion on the public production of medicines in light of the country's current industrial policy and highlights the need to define priority drugs and the role of OPL in guaranteeing access to them.